Beginning Hibernate 6 java persistence from beginner to pro - Ottinger, Joseph B.; Linwood, Jeff; Minter, Dave (Apress, 2022)
Get started with Hibernate, an open source Java persistence layer and gain a clear introduction to the current standard for object-relational persistence in Java. This updated edition includes the new Hibernate 6.0 framework which covers new configuration, new object relational mapping changes, and enhanced integration with the more general Spring, Boot and Quarkus and other Java frameworks. The book keeps its focus on Hibernate without wasting time on nonessential third-party tools, so youll be able to immediately start building transaction-based engines and applications. Experienced authors Joseph Ottinger with Dave Minter and Jeff Linwood provide more in-depth examples than any other book for Hibernate beginners. They present their material in a lively, example-based mannernot a dry, theoretical, hard-to-read fashion. You will: Build enterprise Java-based transaction-type applications that access complex data with Hibernate Work with Hibernate 6 using a present-day build process Integrate into the persistence life cycle Search and query with the new version of Hibernate Keep track of versioned data with Hibernate Envers.
Includes index. - Print version record
Keywords: Hibernate (Electronic resource); Java (Computer program language); Database management -- Computer programs; Database Management Systems; Java (Langage de programmation); Bases de données; Gestion; Logiciels; Database management; Computer programs